Shelf-life study of an infusion of Hibiscus rosa-sinensis, Mentha piperita L. and Citrus sinensis peel - Pizan Cisneros, Kevin Abel; Silva Chuquipoma, Diego Honorato (LACCEI, 2025)
Infusions are especially hot beverages made from natural plants, fruits and shells in dehydrated form, maintaining their initial functional and medicinal properties. Therefore, the objective of this study was to determine the shelf life of a filtering infusion of Hibiscus rosa-sinensis, Mentha pipireta L and Citrus sinensis peel. Samples were packed in cardboard boxes and packed with cellophane plastic, which were stored in a drying hood at 22ºC for 45 days. A sensory card with a hedonic scale from 0 to 5 was used as an instrument, considering a score of 2 as a critical value, using 10 trained panelists and subsequently the mathematical model of Wyser and Lanctuit was used. The results on the sensory scale in the sixth fortnight presented a score of 2 as a critical value, which obtained 19.85% moisture and 0.72 water activity; likewise, the samples complied with the microbiological values with 110 CFU/g for Enterobacteriaceae and